The Usage of Artificial Neural Networks For Finite Capacity Planning - Guneri, Ali Fuat; Gumus, Alev Taskin (UNIV CINCINNATI INDUSTRIAL ENGINEERING, 2008)
In this study finite scheduling and artificial neural networks are applied for finite capacity planning. Utilisation of artificial neural networks on solving finite scheduling problems is examined. Also a model is developed by using multi layer perceptron (MLP) networks and carried out to solve a real world problem in a job shop scheduling system, in an automotive firm. Significance: Finite capacity scheduling and its integration with the other functions of the companies is very important to manage planning activities in manufacturing. The usage of artificial neural networks in finite scheduling is studied in this paper.
Keywords: Finite capacity scheduling; Artificial neural networks; Multi layer perceptron; APPROXIMATION; Engineering